Improving adherence to acne treatment: the emerging role of application software - Park C; Kim G; Patel I; Chang J; Tan X (Dove Medical Press, 2014)
Chanhyun Park,1 Gilwan Kim,1 Isha Patel,2 Jongwha Chang,3 Xi Tan2 1College of Pharmacy, University of Texas at Austin, Austin, TX, USA; 2College of Pharmacy, University of Michigan, Ann Arbor, MI, USA; 3McWhorter School of Pharmacy, Samford University, Birmingham, AL, USA Objective: To examine recent studies on the effect of mobile and electronic (ME)-health technology on adherence to acne treatment. Background: With emerging use of ME-health technology, there is a growing interest in evaluating the effectiveness of the tools on medication adherence. Examples of ME-health technology-based tools include text message-based pill reminders and Web-based patient education. Methods: MEDLINE, Cochrane Library, and Web of Science were searched for articles on adherence to acne treatment published through November 2013. A combination of search terms such as "acne" and "adherence" or "compliance" were used. Results: Adherence to oral acne medication was higher than for topical acne medication. The frequency of office visits was also an influencing factor for acne treatment adherence. The telephone-based reminders on a daily basis did not improve acne patients' medication adherence, whereas the Web-based educational tools on a weekly basis had a positive effect on medication adherence in acne treatment. Conclusion: In using ME-health interventions, factors such as medication dosage forms, frequency of intervention, and patients' preferences should be taken into consideration. Developing disease-specific text message reminders may be helpful to increase adherence rates. In addition, a combination of text message reminders with another type of intervention may improve medication adherence. Keywords: acne vulgaris, medication adherence, compliance, mobile and electronic health technology, application software, telemedicine